Immunological Markers for PML Prediction in MS Patients Treated with Natalizumab - Antoniol, Caroline; Stankoff, Bruno (Frontiers in Immunology, 2015)
Natalizumab, a monoclonal antibody recognizing the alpha4 integrin chain, has been approved for the treatment of active multiple sclerosis, but expose to the onset of a rare side effect, progressive multifocal leurokoencephalitis (PML). Estimating the individual risk of PML in natalizumab-treated patients is a major challenge, and therapeutic strategies are mainly guided by the overall PML risk assessed by identified risk factors: JCV seropositivity, treatment duration (with peak incidence after 24 months) and the previous use of immunosuppressive therapies. Given that this stratification does not yet allow a precise individual prediction of PML, other predictive markers are needed, and several immunological biomarkers have been described. Quantification of anti-JCV antibody levels may improve individual predictive value, with higher baseline titers indicating increased risk. Other immunological biomarkers such as leukocyte cell membrane markers (CD49d, CD11a, CD62L), detection of circulating JCV-specific activated T effector memory cells (TEM) or genetic screening have been proposed. In this review, we discuss how recent progress in immunology has paved the way for «new combined monitoring», which will include immunological screening, in natalizumab-treated patients